2021
DOI: 10.3390/jcdd8110135
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cardiac Small Extracellular Vesicle-Derived Vehicles with Thin-Film Hydration for Customized microRNA Loading

Abstract: Cell therapies for myocardial infarction, including cardiac ckit+ progenitor cell (CPC) therapies, have been promising, with clinical trials underway. Recently, paracrine signaling, specifically through small extracellular vesicle (sEV) release, was implicated in cell-based cardiac repair. sEVs carry cardioprotective cargo, including microRNA (miRNA), within a complex membrane and improve cardiac outcomes similar to that of their parent cells. However, miRNA loading efficiency is low, and sEV yield and cargo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Thirty hours before sEV collection, cells were treated with the 1:1 mixture of Lipofectamine 2000 (Thermo Fisher Scientific) and MISSION Synthetic microRNA inhibitor (Sigma-Aldrich) for miRNA depletion under serum starvation in serum-free Ham’s F-12 medium. After 6 hours of miRNA inhibitor treatment, the medium was changed to fresh serum-free Ham’s F-12 medium and collected after 24 hours to isolate sEVs by sequential ultracentrifugation as previously described ( 17 ). All sEVs were resuspended in 300 μl of PBS and were quantified using nanoparticle tracking analysis on NanoSight NS300 (Malvern Panalytical, Malvern, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty hours before sEV collection, cells were treated with the 1:1 mixture of Lipofectamine 2000 (Thermo Fisher Scientific) and MISSION Synthetic microRNA inhibitor (Sigma-Aldrich) for miRNA depletion under serum starvation in serum-free Ham’s F-12 medium. After 6 hours of miRNA inhibitor treatment, the medium was changed to fresh serum-free Ham’s F-12 medium and collected after 24 hours to isolate sEVs by sequential ultracentrifugation as previously described ( 17 ). All sEVs were resuspended in 300 μl of PBS and were quantified using nanoparticle tracking analysis on NanoSight NS300 (Malvern Panalytical, Malvern, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In this manner, sEVs play a critical role in cell therapy by delivering molecular cargo and mediating intercellular or interorgan signaling (17). The beneficial effects of sEV have been largely attributed to cargo microRNA (miRNA): short noncoding RNA that binds mRNA and induces degradation (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We explored electroporation as a method for CPC-derived ELV synthesis to build upon our previous work using thin-film hydration. 18 Electroporation uses small voltage pulses to create temporary openings in the vesicle membrane and allows the miR cargo of choice to be encapsulated into the vesicle through a diffusion gradient (Figure 1A). We confirmed that the shape of the synthesized ELVs was similar to that of CPC sEVs by using transmission electron microscopy (Figure 1B).…”
Section: Cpc-derived Elvs Synthesized With Electroporationmentioning
confidence: 99%
“…Given that the ELVs in our prior published work formed by self-assembly, controlling the amount of cargo loaded was challenging. 18 To enhance the scalability and versatility of ELVs as customized cargo-carrying vehicles, we explored the potential tunability of miR loading with electroporation. First, we optimized the sEV inherent RNA cargo depletion to provide vesicles with "cargo-free" cavities from which to synthesize the ELVs.…”
Section: Cpc-derived Elvs Synthesized With Electroporationmentioning
confidence: 99%